Heavy Metal Levels in Cladophora glomerata which Seasonally Occurrence in the Lake of Hazar - Alp, Mehmet Tahir; Sen, Bulent; Ozbay, Ozgur (Foundation Environmental Protection & Research-Fepr, 2011)
Heavy metal accumulations in algal species are generally studied under laboratory conditions. However, there is rather limited knowledge on heavy metal accumulation of micro algal species in their natural habitats. In this study, some heavy metal loads absorbed by C. glomerata which shows intensive population in late spring and early summer in the littoral zone of the Lake Hazar, which is a relatively oligotrophic, and has a high alkaline level, were investigated. Obtained data were compared with heavy metal loads of the water. Levels of heavy metals in the algae were found as 1,31-1,77 mg/g- C. glomerata for Cupper (Cu), 58,5-218 mg/g- C. glomerata for Iron (Fe), 2,75-4,99 mg/g- C. glomerata for Manganese (Mn) and 9,61-11,8 mg/g- C. glomerata for Zinc (Zn). In conclusion, C. glomerata absorbs some heavy metals which are dangerous for human health. Therefore, this species has a potential to be use as bio-absorbent in waste water treatments.
Hazar gölü'nde mevsimsel olarak ortaya çikan cladophora glomerata' da bazi a?ir metal düzeyleri
Keywords: Cladophora glomerata; Clorophyta; Heavy metal; Lake Hazar